Comparison of the Creative Thinking Abilities of Class XI High School Students on Environmental Pollution Material Given Gender Differences - Rida Amaliah; Arsad BAHRI (RADINKA JAYA UTAMA PUBLISHER, 2024)
Creative thinking skills are skills that develop an idea or ideas based on existing problems or solve problems from various points of view. The results of the 2015 GCI survey show that the creative thinking ability of Indonesian people is still low, ranking 86th in the creative class 93 countries. This research aims to determine the creative thinking abilities of high school students regarding environmental pollution material in terms of gender differences. This type of research is descriptive research with a quantitative approach. The research subjects were class XI students of SMA Negeri 4 Sidrap for the 2023–2024 academic year, with a sample of 30 students. The sample was determined by random sampling. Data collection techniques use tests. The data analysis technique uses descriptive statistical processing. The results of the research show that the percentage score of students' creative thinking ability on the indicators of fluency is 65.52%, originality is 71.97%, flexibility is 69.97%, and elaboration is 73.64%.